Socioeconomic inequalities in HIV testing uptake in sub-Saharan Africa : A multi-country analysis of population-based surveys - (:unkn) unknown (My University, 2022)
HIV testing plays a critical role in the fight against HIV/AIDS. Successful scale-up of HIV testing services insub-Saharan Africa (SSA) has increased the overall proportion of HIV testing uptake in recent years. However,such an overall increase may hide important disparities across socioeconomic positions (SEP). The overall aimof this thesis is to investigate socioeconomic inequalities in HIV testing uptake through multi-country analysisof nationally representative and standardized population-based surveys in SSA. More specifically, this thesisaimed at: i) quantifying socioeconomic inequalities in HIV testing uptake and assess their trends over time; ii)exploring the spatial distribution of socioeconomic inequalities in HIV testing uptake across various geographicalscales; iii) identifying contextual factors associated with socioeconomic inequalities in HIV testing uptake; andiv) understanding the mediating pathways linking SEP to HIV testing uptake at the individual level in severalSSA countries. The findings of this thesis may be useful in designing well-tailored HIV testing strategies that donot generate nor worsen inequalities.
Keywords: African Research